THE SIMPLIFICATION OF THE ENGLISH LANGUAGE IN DIGITAL COMMUNICATION AND ITS LINGUISTIC FEATURES - Qodirova , Dilnura; Saitov , Sirojiddin (Scientific practical conference, 2026)
This article examines the simplification of the English language in digital communication and its linguistic features. In the era of rapid technological development and widespread use of social media, digital communication has significantly influenced language structure, vocabulary, and usage. The study analyzes the main characteristics of simplified English in online environments, including abbreviations, acronyms, emojis, and grammatical reduction. It also explores the emergence of new lexical items (neologisms), the role of informal language, and stylistic changes in communication. Furthermore, the article highlights both positive and negative impacts of language simplification on communication efficiency, language learning, and linguistic norms. The findings suggest that while digital communication promotes speed and convenience, it also contributes to the transformation of traditional language structures.